Extração em fase sólida magnética de bisfenol A utilizando híbrido CoFe2O4/MON/Grafeno - Oliveira, Rhayza Victoria Matos (2021)
This work consisted in synthesizing magnetic hybrid materials consisting of cobalt ferrite, natural organic matter and graphene (CoFe2O4 /NOM/Graphene), and applying it as an adsorbent in the analytical methodology of BPA magnetic extraction in aqueous matrices. Initially, four hybrid materials were synthesized: ferrite from chloride (HFC), ferrite from sulfate (HFS), graphene from chloride (HGC) and graphene from sulfate (HGS). The X-ray diffraction technique demonstrated the formation of the cobalt ferrite phase in all synthesized materials, as well as that of graphene in hybrids. Spectroscopy in the infrared region revealed the presence of functional groups by stretching the O-H and C = O bonds characteristic of the presence of NOM, C = C of graphene, in addition to Fe-O of the ferrites. Transmission electron microscopy images revealed spherical nanoparticles with dimensions of 9.72 nm (HFC), 34.0 nm (HFS); 8.75 nm (HGC) e 43.9 nm (HGS). In addition, graphene sheets were observed in a few layers. Raman spectra confirmed the formation of cobalt ferrite, highlighting its inverse spinel type, and indicated the formation of graphene. The graphene formed showed few structural defects, and the number of layers was estimated as mono and double layer. The adsorption experiments showed the potential of graphene hybrids in the adsorption stage, 94.19% (HGS) and 97.95% (HGC). Optimization of this step resulted in the use of 50 mg of HGC and orbital agitation at 150 rpm for 5 minutes. Desorption was performed in 2.5 minutes at 150 rpm, using methanol as solvent, obtaining 99.19% of BPA desorbed. The analytical validation showed a correlation coefficient r = 1.00, LD = 0.022 μg L-1 and LQ = 0.072 μg L-1 . The reproducibility of the extraction procedure varies from 2.13 - 2.21% and shows excellent recoveries in the range of 99.33 – 104.4%. The method proved to be feasible for application in bottled, river and supply water samples with recoveries of 99.87 - 104.7%. Furthermore, the MSPE methodology used proved to be simple, fast and efficient for the extraction of BPA in aqueous matrices, in addition to the use of an eco-friendly adsorbent as a support.